Studies on the metabolic clearance rate and production rate of human luteinizing hormone and on the initial half-time of its subunits in man. - Pepperell, R J (1975)
The metabolic clearance rate (MCR) of human luteinizing hormone (hLH) has been determined in 10 normal men, 3 normal women, and in 12 women with ovulatory disorders resulting in oligomenorrhea or amenorrhea. The MCR was determined by the constant infusion technique using either iodinated or unlabeled highly purified hLH, and these results were compared to MCR determined by using crude pituitary preparations containing both follicle-stimulating hormone and hLH. Both preparations produced essentially similar results for the MCR of hLH and virtually identical results were obtained when complete or incomplete immunoprecipitation of the infused material was achieved. The MCR/body surface area of hLH was significantly greater in normal men (25.6 plus or minus 3.6 ml/min-m-2) than in normal premenopausal (19.2 plus or minus 0.9 ml/min-m-2) or postmenopausal women (17.4 plus or minus 1.9 ml/min-m-2). No difference was noted in the MCR of hLH in women with oligomenorrhea or amenorrhea. Production rates (PRs) were calculated by using a pituitary standard, the values being 85.1 plus or minus 21.5 IU/24 h in normal men, 39.9 plus or minus 12.6 IU/24 h in normal premenopausal women, and 294.6 plus or minus 61.9 IU/24 h in normal postmenopausal women. The initial half-times of disappearance of the alpha- and beta-subunits of hLH were measured in two normal men and found to be 15-18 min, respectively. The half-time of intact hLH was twice as great.